Impact of intense sanitization procedures on bacterial communities recovered from floor drains in pork processing plants - Bosilevac, Joseph M.; Guragain, Manita; Barkhouse, Darryll A.; Velez, Sarah E.; Katz, Tatum S.; Lu, Guoqing; Wang, Rong (Frontiers in Microbiology, 2024)
Pork processing plants in the United States (US) cease operations for 24-48 hours every six or twelve months to perform intense sanitization (IS) using fogging, foaming, and further antimicrobial treatments to disrupt natural biofilms that may harbor pathogens and spoilage organisms. The impact such treatments have on short-term changes in environmental microorganisms is not well understood, nor is the rate at which bacterial communities return. Swab samples were collected from floor drains to provide representative environmental microorganisms at two US pork processing plants before, during, and after an IS procedure. Samples were collected from four coolers where finished carcasses were chilled, and from four locations near cutting tables. Each sample was characterized by total mesophile count (TMC), total psychrophiles (TPC), and other indicator bacteria; their biofilm forming ability, tolerance of the formed biofilm to a quaternary ammonium compound (300ppm, QAC), and ability to protect co-inoculated Salmonella enterica. In addition, bacterial community composition was determined using shotgun metagenomic sequencing. IS procedures disrupted bacteria present but to different extents depending on the plant and the area of the plant. IS reduced TPC and TMC, by up to 1.5 Log10 CFU only to return to pre-IS levels within 2–3-days. The impact of IS on microorganisms in coolers was varied, with reductions of 2-4 Log10, and required 2 to 4 weeks to return to pre-IS levels. The results near fabrication lines were mixed, with little to no significant changes at one plant, while at the other, two processing lines showed 4 to 6 Log10 reductions. Resistance to QAC and the protection of Salmonella by the biofilms varied between plants and between areas of the plants as well. Community profiling of bacteria at the genus level showed that IS reduced species diversity and the disruption led to new community compositions that in some cases did not return to the pre-IS state even after 15 to 16 weeks. The results found here reveal the impact of using IS to disrupt the presence of pathogen or spoilage microorganisms in US pork processing facilities may not have the intended effect.